ANALYZING THE EFFECT OF INVESTMENT, WORKFORCE, HUMAN DEVELOPMENT INDEX, AND GOVERNMENT EXPENDITURES IN THE ECONOMIC GROWTH OF EAST JAVA PROVINCE - GURNING, HANS MARTIN (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aims to determine whether investment, labor, HumanDevelopment Index and government expenditures influence economic growth in EastJava. Hence, the results of this research can determine whether these variables havesignificant influence or not. This research contains investment, labor, HumanDevelopment Index, and government expenditures influence economic growth in EastJava Province. Secondary data and from several sources such as the Central Bureauof Statistics, Directorate General of Fiscal Balance are the data used in this research.Also, this research uses quantitative research because it uses data in the form ofnumbers and uses tools to analyze information. The tool used Eviews 9. This researchused data as much as five years, starting from 2012 to 2016. Dependent variable (Y)in this research is economic growth, while the independent variables in this researchare investment, labor, Human Development Index, and government expenditures. Theresults of this research indicate that investment and labor do not have a significanteffect on the economic growth in East Java Province. Meanwhile, the HumanDevelopment Index and government expenditures influence East Java economicgrowth.Keywords: economic growth, investment, labor, Human Development Index,government expenditures